2009
DOI: 10.2147/pgpm.s4865
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the A118G polymorphism of the mu opioid receptor gene (OPRM1) and opioid  dependence: A meta-analysis

Abstract: Mu opioid receptor (OPRM1) gene variants, particularly the common A118G single nucleotide polymorphism (SNP), are among the most frequently studied candidate genes associated with opioid dependence. However, despite numerous case-control studies and metaanalyses, no defi nitive conclusion has been reached regarding the association of the A118G SNP and risk of developing opioid dependence. This study aimed to resolve this discrepancy by reinvestigating the association between A118G SNP allelic, and for the fi r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Furthermore, numerous meta-analyses reported that the G allele of rs1799971 is associated with alcohol, opioid, cannabis, cocaine, and nicotine addictions. However, the reported association between the G allele and drug addictions has been inconsistent (Arias et al, 2006;Chen et al, 2012;Coller et al, 2009;Glatt et al, 2007;Haerian and Haerian, 2013;Schwantes-An et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous meta-analyses reported that the G allele of rs1799971 is associated with alcohol, opioid, cannabis, cocaine, and nicotine addictions. However, the reported association between the G allele and drug addictions has been inconsistent (Arias et al, 2006;Chen et al, 2012;Coller et al, 2009;Glatt et al, 2007;Haerian and Haerian, 2013;Schwantes-An et al, 2016).…”
Section: Introductionmentioning
confidence: 99%